INCLUSIVE GOVERNANCE OF GENDER AND SOCIO-ECONOMIC POLICIES : A RATIONAL-COMPREHENSIVE APPROACH IN ACEH - Nellis Mardhiah; Noka Omalia; Cut Annisa Fitriati; Zikri Muhammad (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the development of gender inequality issues and solutions in Aceh, focusing on the principle of inclusiveness. This study also describes several ways to take action to address gender inequality and form alternative sustainable gender policy options in Aceh. The research method used is qualitative, with a case study approach that focuses on developing gender issues and policy directions in Aceh. The study results show that the development of issues related to gender disparity in Aceh is still high, thus requiring comprehensive solutions in the form of policies. Therefore, several courses of action are needed to solve the problem through women's empowerment. In addition, the Aceh government's commitment to community empowerment is expected to lead to change through an inclusive and equitable approach with a socio-economic perspective in the direction of GEDSI (Gender Equality Disability, and Social Inclustion) policy. This also needs to be realized immediately to improve the protection of women in Aceh, which is expected to be integrated into the RPJMA document, and data-based monitoring must be implemented to maintain accountability.